Traffic analyzer using image processing - Ayub, Adi Abadi (2008)
Traffic analyzer using image processing is PC based window application which capable to analyze traffic parameter such as vehicle rate by using image processing technique. Input of this application is video file which contain captured video on all top view of road. This program will fragment that video file to be several number of frame image. The image will be masked to remove irrelevant area so that not influence further processing. Captured present image and background image will be compared to extract foreground object which is usually a vehicle. Then, segmentation process will evaluate that compared image to get presence of the vehicle. Segmented image always come with noise. For this reason, median filtering is applied to segmented image to get clearer image. Then, object filtration processor will process filtered image to filter the vehicle on the image. Object filtration is based on object size in the image. Then, that frame will compare with previous frame to acquire the number of new vehicle in a present frame. That acquisition number of new vehicle in a frame will increment the present vehicle counter register.